A method for improving the structure and slurry stability of sodium layered oxide and its application

By forming a new sodium salt coating on the surface of the sodium ion layered oxide material, the problem of structural instability of the material during charging and discharging is solved, the energy density and cycling performance of the battery are improved, and the energy consumption cost is reduced.

CN118970015BActive Publication Date: 2025-04-25HENGYANG BST POWER
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411291765.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-04-25
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Sodium ion layered oxide materials are prone to phase change during charging and discharging, resulting in structural instability and affecting the energy density, cycling performance and cost of the battery.

Method used

By mixing the ammonium salt with the layered oxide material and grinding and melting at high temperature, a new sodium salt coating is formed to uniformly cover the particle surface of the layered oxide material, improving the air stability and electrochemical properties of the material.

Benefits of technology

It improves the energy density, circulation performance, and reduces energy consumption costs, and enhances the structural stability and electrical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118970015B_ABST
    Figure CN118970015B_ABST
Patent Text Reader

Abstract

The present invention provides a method for improving the structure and slurry stability of sodium-based layered oxides and its application. The sodium-based layered oxide positive electrode material provided by the present invention comprises a modified matrix material and a phosphorus-containing compound modified on the surface of the matrix material particles. In the present invention, after the phosphorus-containing ammonium salt and the layered oxide material are ground and mixed, they can be evenly covered on the particle surface of the layered oxide material by high-temperature melting and form a new phosphorus-containing compound, which effectively improves the structural stability of the material and improves the slurry gelation problem during the coating process, thereby improving the battery cycle performance; while the ammonium salt removes the ammonia group, it combines with the Na in the layered oxide material to form a new conductive sodium salt, which can improve the energy density and cycle performance of the sodium ion battery (SIB) and reduce the energy consumption cost while retaining the inherent advantages of the O3 phase oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and more specifically, to a method for improving the stability of a sodium-ion layered oxide structure and a slurry containing the sodium-ion layered oxide structure and an application thereof. Background Art

[0002] Today, lithium-ion (LIB) batteries are the main power source for handheld electronics and are considered to be promising energy storage devices to power the next generation of electric vehicles, hybrid electric vehicles. However, limited reserves and uneven distribution of lithium sources in the earth's crust make the domestic lithium supply chain unstable. The increasing consumption of lithium resources has prompted researchers to explore sustainable alternatives in energy storage devices. Due to the easy availability and abundance of Na resources, sodium-ion batteries (SIBs) have attracted great attention as promising candidates for large-scale energy storage.

[0003] Layered sodium intercalated transition metal oxide cathodes are currently popular layered Li x Sodium substitutes for TMO2 cathodes are expected to provide excellent electrochemical performance due to their stable solid-state intercalation reactions and large two-dimensional metal ion diffusion paths. In addition, the structure of layered transition metal oxide cathode materials is customizable. Layered transition metal oxides with target structures can be prepared through appropriate component modulation and process conditions, and therefore have attracted widespread attention. Sodium-ion layered oxides NFM, namely Na x TMO2 (0<x≤1), TM usually refers to transition metals (Fe, Ni, Co, Mn), which can be divided into O3-type and P2-type crystal structure families, which are considered to be one of the most attractive structure types due to their low cost, high theoretical capacity, large operating potential, and simple synthesis process. Compared with P2-type sodium-deficient materials, O3-type materials have higher theoretical energy density and are less dependent on excess sodium at the anode. However, compared with Li analogs, these types of crystal structures have poor performance under Na+ conditions, especially when charged to the cutoff voltage. + The extraction / insertion process often undergoes complex phase transitions. O3-type oxides usually undergo more complex phase transitions than P2-type oxides. Most of the studied O3-NaTMO2 materials undergo two main phase transitions ( Figure 1 ), (a) reversible O3 Na ~ 0.5 TMO2 and (b) irreversible P3Na ~0.5 TMO2-X Na y MO2, where y and X vary with the nature of the TM and the voltage window. However, with Li + In comparison, Na + The ionic radius of Na + The insertion / extraction process will cause multiple structural evolutions, resulting in the deterioration of the layer oxygen crystal structure and poor cycling stability.

[0004] In recent years, efforts have been made to further improve the structural stability and electrochemical performance of sodium-ion layered oxides (NFMs) at working voltages in order to narrow the energy density gap between SIBs and LIBs. However, in actual production, layered oxide cathode materials have strong hygroscopicity. In an environment with a humidity of more than 10%, they can easily react with water and CO2 on the particle surface to generate NaOH and Na2CO3, which is manifested in the following aspects: (1) The surface alkalinity becomes stronger, making it difficult to prepare a stable slurry and coat the electrode uniformly; (2) The formed NaOH and Na2CO3 are insulating, resulting in poor electron conduction, increased battery polarization, and decreased capacity; (3) The water molecules embedded in the layer will trigger side reactions with the electrolyte through the following reactions: NaPF6→NaF+PF5(1); PF5+H2O→POF3+2H(2). Therefore, the hygroscopicity of sodium-ion layered oxides greatly limits the key performance indicators of SIBs such as energy density, cycle performance, and cost.

[0005] In order to improve the structural stability of the material during electrochemical operation and stabilize the cathode slurry viscosity during the coating process, CN116682937A forms a hydrophobic organic coating on the surface of the O3 phase layered oxide, which can protect the O3 phase layered oxide material from phase change side reactions, improve structural stability, and thus improve cycle performance. CN116190633B controls the average value of the interlayer spacing of the O3 phase crystal plane by controlling the content of Na, Cu, and Mn elements in the material and process conditions to improve the structural stability of the material. Patent CN117546316A improves the air stability of the layered oxide material by coating the surface of the base material with an ammonium salt sodium layer. CN116525832A improves the fluidity and stability of the positive electrode slurry by using nitrile rubber, acrylonitrile, and acrylic adhesives or mixing them with PVDF. CN202310579958.X effectively prevents the formation of gel in the positive electrode slurry by adding an inorganic compound-cerium-based compound to the positive electrode slurry, thereby improving the slurry fluidity. Although the existing technologies have paid attention to the poor chemical stability of the O3 phase, they all maintain the stability of the layered oxide material at the expense of ion conductivity and rate performance; and in order to improve the slurry stability, additives are added to the positive electrode slurry, which is not conducive to the high-capacity design of batteries with O3 materials as the positive electrode.

[0006] Based on this, it is necessary to propose a new strategy to modify the O3 phase layer oxygen cathode material, improve its chemical stability from the material itself, improve the processing performance of the prepared slurry, and thus improve the energy density, cycle performance and reduce the energy consumption cost of sodium ion batteries (SIBs). Summary of the invention

[0007] To achieve the purpose of the invention, the present invention provides a method for improving the structure and slurry stability of sodium-containing layered oxides and its application, which can improve the energy density, cycle performance and reduce energy consumption costs of sodium-ion batteries (SIBs) while retaining the inherent advantages of O3-phase oxides. The sodium-containing layered oxide material of the present invention is prepared by grinding and mixing ammonium salts with layered oxide materials, and then melting at high temperature to evenly cover the particle surface of the layered oxide material and form a new sodium salt. The method of the present invention effectively improves the air stability of the prepared material, thereby improving the cycle performance; while the ammonium salt removes the ammonia radical, it combines with the Na in the layered oxide material to form a new conductive sodium salt, which can improve the energy density, cycle performance and reduce energy consumption costs of sodium-ion batteries (SIBs) while retaining the inherent advantages of O3-phase oxides.

[0008] To achieve the above object, the technical solution of the present invention is as follows:

[0009] In one aspect, the present invention provides a sodium-electrolyte layered oxide positive electrode material, comprising a matrix material and a phosphorus-containing compound modified on the surface of the matrix material particles.

[0010] Furthermore, the matrix material is prepared by mixing solid powder, sodium carbonate and CNTC and then calcining them.

[0011] Furthermore, the chemical formula of the solid powder is NaTM x O2, TM is selected from one or more elements of Fe, Cu, Mg, Ni, Mn, Ti, Al, Li, Co, V, Zn, Sb, and Sn, wherein 0.5<x<1, and more preferably 0.8<x<0.9.

[0012] Furthermore, TM is selected from one or more of Fe, Cu, Mg, Ni, Mn, Ti, Al, Li, Co, V, Zn, Sb, and Sn elements; wherein TM is further preferably a combination of Ni, Fe, and Mn, wherein the stoichiometric ratio is 0.2<Ni<0.35, 0.2<Fe<0.35, and 0.2<Mn<0.35.

[0013] Furthermore, the mass ratio of the solid powder, sodium carbonate and CNTC is 100:5:1.

[0014] Further preferably, the layered oxide positive electrode material is an O3 type material.

[0015] Furthermore, the mass ratio of the matrix material to the phosphorus-containing compound is 100:(0.1-2), and more preferably 100:1.

[0016] On the other hand, the present invention provides a method for improving the structural stability of the sodium-electrode layered oxide positive electrode material, comprising the following steps:

[0017] S1: Mn source, Fe source and Ni source are uniformly mixed and dissolved in a stoichiometric ratio to obtain a TM salt solution, and the solid powder, sodium carbonate and CNTC are mixed and calcined to obtain a matrix material after the action of a coprecipitant;

[0018] S2: mixing and grinding the base material and the ammonium salt;

[0019] S3: The mixture obtained in S2 is sintered and cooled.

[0020] Furthermore, the Mn source, Fe source and Ni source are uniformly mixed in a stoichiometric ratio to prepare 0.6 mol L -1 TM salt solution, wherein 0.2<Ni<0.35, 0.2<Fe<0.35, 0.2<Mn<0.35.

[0021] Furthermore, the Mn source, Fe source and Ni source are all corresponding nitrates.

[0022] Further, the TM salt solution is mixed with a coprecipitant to obtain a solid powder. Further, the coprecipitant is selected from one or more of sodium carbonate, sodium hydroxide, ammonium carbonate, and sodium bicarbonate. Further, the coprecipitant is a mixture of sodium carbonate and sodium hydroxide, and the mass ratio of the two is (20-25):1, preferably (20-21):1, for example 20.92:1.

[0023] Furthermore, the solid powder, sodium carbonate and CNTC are mixed and calcined in an oxygen atmosphere to obtain a matrix material. Furthermore, the mass ratio of the solid powder, sodium carbonate and CNTC is 100:(1-10):(0.5-3), preferably 100:5:1. Furthermore, the solid powder, sodium carbonate and CNTC are mixed and vacuum dried for 12 hours. Furthermore, the calcination process is: 1-5°C min -1 Heat to 500-600℃ and calcine for 1-5h, at 1-5℃min -1 The temperature is raised to 900-1000°C and kept at this temperature for 5-12 hours. Preferably, the calcination process is: -1 Heat to 500℃ and calcine for 3h, at 3℃min -1 Raise the temperature to 900℃ and keep it for 9h.

[0024] Further, the mass ratio of the base material to the ammonium salt is 1:(80-120), and more preferably 1:100. Further, the grinding time is 15-25 min, and preferably 20 min. Further, the ammonium salt is selected from one or more of diammonium phosphate, ammonium hydrogen phosphate, ammonium phosphate and ammonium polyphosphate.

[0025] Furthermore, the sintering process is: heating in an inert atmosphere at 1-5°C min -1 The temperature is raised to 300-400°C and kept at this temperature for 1-6 hours. Preferably, the sintering process is: heating in an argon atmosphere at 3°C ​​min -1 Keep warm at 300℃ for 4h.

[0026] On the other hand, the present invention provides a positive electrode slurry, which is a positive electrode composition for a sodium ion secondary battery, comprising the layered oxide positive electrode material of the present invention.

[0027] In another aspect, the present invention provides a sodium ion secondary battery, comprising the positive electrode slurry of the present invention.

[0028] In another aspect, the present invention provides a use of a sodium ion secondary battery in an energy storage device.

[0029] Beneficial effects:

[0030] In order to improve the gelation problem of the slurry during coating and to improve the stability in the electrolyte during battery operation, surface modification is necessary. Ammonium salt coatings have received special attention due to their low cost and high conductivity, but have not yet been explored for O3 sodium layered oxide materials. Due to the melting properties of ammonium dihydrogen phosphate at 300°C, liquid ammonium salts can diffuse to the surface of layered oxide particles and form a uniform coating, and new sodium salts can be formed at high temperatures, showing a flexible modification ability for O3 layered oxide materials, which can effectively improve the structure of the material and thus improve the degradation problem during battery preparation and operation.

[0031] Compared with the adverse effects caused by the thickness of the coating layer introduced in the prior art, the sodium salt coating formed on the surface of the O3 phase has a thin thickness. When preparing the sodium salt, the proportion of ammonium salt can be reduced to control the thickness and distribution uniformity, which can effectively modify the O3 layered oxide positive electrode material.

[0032] After the prior art introduces the coating layer, it is inevitable to introduce the interface problem between the coating layer and the layered oxide, which affects its ionic conductivity, and may also increase the expansion coefficient during the charge and discharge process, causing material damage or shedding problems. The present application achieves uniform coating by mixing ammonium salt with layered oxide particles, which can effectively maintain the stability of layered oxide particles, and the ammonium salt can react in situ with the sodium salt remaining on the surface of the base material after deamination to generate a sodium salt with better conductivity and more stable, so that there is no interface problem between the coating layer and the core of the base material, not only the electrolyte is carried, but also the surface activity of the positive electrode material can be reduced, the stability of the material when in contact with air is improved, and the rate performance and cycle performance of the material are improved. Even if the material of the present invention absorbs moisture, the water molecules are also on the periphery of the material, which can be physically baked and removed to improve the stability of the material when in contact with air.

[0033] Compared with the coating layer in the prior art, the present invention mixes ammonium salts with layered oxide particles by bulk doping, thereby stably reducing cracks in the O3 structure. At the same time, the melting properties of ammonium salts at a certain temperature are utilized. For example, ammonium dihydrogen phosphate will melt at 300°C, thereby achieving automatic diffusion of liquid ammonium salts, and then covering the surface of the layered oxide particles to achieve uniform coating, thereby solving the problem of poor thickness uniformity in the prior art, and effectively achieving uniform coating while removing residual alkali on the surface of the material; the partial decomposition products of the ammonium salts can combine with the sodium ions in the O3 structure to balance the charge, further reducing the Jahn-Teller effect of heavy metal ions during charging and discharging, thereby solving the problem of rate difference in the prior art.

[0034] After grinding and mixing, the coated ammonium salt and layered oxide material of the present invention can be evenly covered on the particle surface of the layered oxide material by high-temperature melting, effectively improving the air stability of the material, thereby improving the cycle performance; the ammonium salt-coated layered oxide particles can improve the single-amount ion transmission performance of the material, prevent the positive electrode material from directly contacting the electrolyte, effectively inhibit side reactions and the formation of resistive surface films, achieve a dual improvement of the interior and surface of the material, and make the material have excellent electrical properties.

[0035] In the present invention, after the phosphorus-containing ammonium salt and the layered oxide material are ground and mixed, they can be melted at high temperature to evenly cover the particle surface of the layered oxide material and form a new phosphorus-containing compound, which effectively improves the structural stability of the material and improves the slurry gelation problem during the coating process, thereby improving the battery cycle performance; the ammonium salt removes the ammonia radical and combines with the Na in the layered oxide material to form a new conductive sodium salt, which can improve the energy density and cycle performance of the sodium ion battery (SIB) and reduce the energy consumption cost while retaining the inherent advantages of the O3 phase oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1This is a schematic diagram of the typical structural evolution of O3-phase layered oxides during charge and discharge. In the figure, charge is charged; discharge is discharged, or or.

[0037] Figure 2 The preparation process and principle diagram of NFM-2. In the figure, mixed; annealing.

[0038] Figure 3 Scanning electron microscope morphology images of annealed materials with different mass ratios of NFM and NH4H2PO4. Figure 3 a: mass ratio is 100:0, Figure 3 b: mass ratio is 100:0.1, Figure 3 c: mass ratio is 100:0.5, Figure 3 d: mass ratio is 100:1, Figure 3 e: mass ratio is 100:1.5, Figure 3 f: Mass ratio is 100:2; In the figure: residual alkali.

[0039] Figure 4 This is the scanning electron microscope element content analysis diagram of NFM-2.

[0040] Figure 5 Initial charge and discharge curves of button batteries made of different cathode materials at 0.1C. In the figure, Voltage is voltage; Capacity is capacity.

[0041] Figure 6 The electrode is placed at a humidity of 68-71% for 16 hours.

[0042] Figure 7 The initial charge-discharge curves of different positive electrode materials before and after water absorption at 0.1C. In the figure, Voltage is voltage; capacity is capacity. Figure 7 It can be seen that the first discharge capacity of the NFM-H2O sample is only 54.54 mAh g -1 The test results show that the gram capacity of the NFM sample decreased significantly after moisture absorption; the first discharge capacity of the NFM-1 sample decreased the most, indicating that the simple physical blending of the modifier and the layered oxide material cannot improve the structural stability of the layered oxide material, but has the opposite effect. Unlike the previous two materials, the NFM-2 sample showed good water resistance, indicating that the modified material has good structural stability.

[0043] Figure 8 The rate performance of button batteries made of different cathode materials. In the figure, cycle number is the number of cycles; capacity is the capacity. Figure 8As shown in Figure 2, NFM-2 has the best rate performance, with a gram capacity of 95.0 to 101.46 mAh g at a discharge rate of 10C. -1 , which is better than NFM samples (62.21~69.18mAh g -1 ) and NFM-2-H2O samples (83.44~86.81mAhg -1 ). At the same time, it can be found that although the NFM-2 sample has been exposed to air, its rate performance is still better than that of the NFM sample, indicating that the material has been successfully modified.

[0044] Fig. 9 This is the viscosity change diagram of the positive electrode slurry.

[0045] Fig.10 The cycling performance test graphs of NFM sample, NFM-2 sample and NFM-2-H2O material were conducted at a rate of 0.1C.

[0046] The present invention will be further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with specific examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0048] Electrochemical testing:

[0049] All electrochemical tests were performed in a Xinwei test cabinet (CT-3008) at 25°C.

[0050] Chemicals and instruments

[0051] All materials and chemicals were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; 0.1M NaPF6 electrolyte was provided by Shenzhen Xinzhoubang Technology Co., Ltd.; glass fiber (GF / D Whatman); a full set of CR2032 button battery accessories and sodium sheet negative electrode (15.6mm*0.45mm) were purchased from Dongguan Kelude Innovation Technology Co., Ltd.

[0052] The vacuum drying oven (DZF-6020B) was purchased from Shanghai Yixin Scientific Instrument Co., Ltd. The high-temperature tube furnace (OTF-1200X-II) was purchased from Hefei Kejing Material Technology Co., Ltd. Field emission scanning electron microscopy (SEM) tests were performed on Zeiss Sigma 300. The rotational viscometer (NDJ-8S) was purchased from Hunan Lichen Instrument Technology Co., Ltd.

[0053] Example 1 Preparation of positive electrode material

[0054] (1) Preparation of NFM

[0055] According to the molecular formula NaTM 0.85 O2 (TM is Ni, Fe and Mn, Ni is 0.3, Fe is 0.25, Mn is 0.3), analytical purity Mn(II), Fe(III) and Ni(II) nitrates are dissolved in deionized water according to stoichiometric amounts to prepare 0.6 mol L -1 TM salt solution, at the same time, Na2CO3 (5.65 g) and NaOH (0.27 g) were dissolved in 120 mL of deionized water as coprecipitants so that the molar ratio of sodium to transition element TM was 0.955, and solid powder was obtained by filtration;

[0056] The solid powder was mixed with 5% excess Na2CO3 (to make up for the loss of sodium during annealing) and 1% CNTC (carbon nanotubes) based on the weight of the solid powder. After vacuum drying for 12 h, an oxygen flow was introduced into a tube furnace at 3 ° C min -1 After heating to 500℃ for 3h, the temperature was continued to rise at 3℃ min -1 The temperature was raised to 900°C and heated for 9 hours to obtain the sample NFM.

[0057] (2) Preparation of NFM-1

[0058] 8 mg NH4H2PO4 and 0.8 g NFM were mixed and ground in a mortar for 20 min (powder blending) to obtain NFM-1.

[0059] (3) Preparation of NFM-2

[0060] 30 mg NH4H2PO4 and 3 g NFM were mixed and ground in a mortar for 20 min. The powders were then poured into a corundum crucible and placed in a tube furnace and heated in an argon atmosphere at 3 °C min. -1 Heat to 300℃ and keep warm for 4h. Figure 2 shown.

[0061] NH4H2PO4→H3PO4+NH3 (3)

[0062] 3Na2CO3+2H3PO4→2Na3PO4+3CO2+3H2O (4)

[0063] ΔG=ΔH-TΔS (5)

[0064] ΔG Na =ΔH Na -TΔS Na =-184kJ (6)

[0065] It can be seen from reaction equations (3) to (6) that under high temperature conditions, NH4H2PO4 can react with sodium carbonate remaining on the surface of the layer oxygen after thermal decomposition and deamination to generate a more stable phosphorus-containing compound, i.e., a new sodium salt. Nernst equation calculations show that the Gibbs free energy difference for the conversion of sodium carbonate into sodium phosphate is less than zero, and the reaction is thermodynamically feasible (Table 1).

[0066] Table 1 Thermodynamic standard values

[0067] Compound ΔH (kJ / mol) S (J / Kmol) <![CDATA[Na2CO3]]> -1131 135 <![CDATA[Na3PO4]]> -1936 225 <![CDATA[H3PO4]]> -1272 151 <![CDATA[CO2]]> -394 214 <![CDATA[H2O]]> -286 7

[0068] Example 2 Preparation of button cell

[0069] Preparation: Prepare 8% PVDF-NMP glue, for example, 4g PVDF (polyvinylidene fluoride), 50g NMP (N-methylpyrrolidone). Add a magnet to the beaker and stir until there is no particle aggregation in the solution and it becomes a uniform liquid. Seal it when not in use. Bake SP (carbon black) at 100℃ for at least 30 minutes in advance.

[0070] 1. Pulping

[0071] Active material: PVDF: kappa 100 = 8:1:1, blend and grind for 10-15 min. When the humidity in the drying room is less than 10% (dehumidification for 1 h), the positive electrode materials prepared in Example 1 (NFM, NFM-1 and NFM-2) are weighed, put into a mortar (can be put into a drying oven at 100°C for 10 min), repeatedly grind clockwise and counterclockwise for 5-8 min, add the baked SP, grind for 8-10 min (grind thoroughly, otherwise there will be particles when coating), directly scrape the powder into a beaker, put it on a weighing balance and return to zero, add 0.3-0.5 g of the adjusted PVDF-NMP glue, and add 1.2-1.5 g of NMP. Stir for 10-15 min until the slurry is uniform and there are no particles on the glass rod, and obtain the homogenized slurry samples of NFM, NFM-1 and NFM-2 respectively.

[0072] 2. Coating and slicing

[0073] Preparation: Spread the coating scraper and current collector (aluminum foil) on a flat, scratch-free desktop. Wipe the dust on the current collector surface with alcohol (statically adsorb dust in the air or around). If there are scratches on the desktop, place a glass plate under it. 150μm scraper coating, 14mm positive electrode sheet mass is 12~17mg.

[0074] 3. Assemble the battery

[0075] Negative electrode shell (2023#) - spring gasket - sodium sheet (tear off the two sides of the diaphragm, the blue film side faces the spring gasket, and the transparent film side faces the sodium side upward) - 2 drops of electrolyte - ceramic diaphragm - 2 drops of electrolyte - pole piece (the side with material faces down, facing the diaphragm) - positive electrode shell (bamboo clip cover), self-sealing bag sealing, 0.5~0.75MPa pressure sealing. Tighten the knob after each pressing, and wipe the sealing mold and the electrolyte on the pressed battery with dust-free paper.

[0076] The glass fiber separator (GF / D whatman) is relatively thick, with a diameter of 18mm, which is larger than the negative electrode shell. The assembled battery can be adjusted to be active starting from the positive electrode shell, pole piece, electrolyte, and so on.

[0077] (Humidity <10%, 150μm knife edge coating, pole piece baking at 100℃ for 12h, battery pressing pressure 500MPa, glove box water <0.1ppm, oxygen <0.1ppm).

[0078] 4. Process steps

[0079] Positive half-cell: let stand for 6-12h, charge at 0.1C constant current, let stand for 10-15min, discharge at 0.1C constant current.

[0080] Overall, this work provides valuable insights into the unique challenges of surface modification and air stability of Na-O3 oxide materials.

[0081] Parameter Test Example 1 Material Morphology Characterization and Modification Ratio Detection

[0082] In order to obtain the optimal modification amount of NH4H2PO4 in NFM-2, the morphology of high temperature annealed materials with NFM and NH4H2PO4 mass ratios of 100:0, 100:0.1, 100:0.5, 100:1, 100:1.5, and 100:2 were characterized. Figure 3 As shown in a, NFM prepared without adding NH4H2PO4 has small granular substances on its scaly surface. These impurities are sodium residues, such as NaOH and Na2CO3. Figure 3 It can be seen from af that as the amount of NH4H2PO4 added increases, the residual alkali gradually decreases to zero; when the mass ratio of NFM to NH4H2PO4 is 100:1, it is the optimal amount of modifier added. The latter may be due to excessive addition of NH4H2PO4, and the surface of NFM is obviously covered with a layer of glassy substance ( Figure 3 e, f).

[0083] When comparing the materials with a mass ratio of NFM to NH4H2PO4 of 100:0 and 100:1, Figure 3gh shows that the samples present a similar spherical morphology, which is due to the accumulation of flaky primary particles; the diameter is 14μm~15μm, which shows that the surface treatment does not affect the overall spherical morphology of the particles.

[0084] In order to further detect the traces of the modifier, SEM-EDS elemental analysis was performed on the materials, such as Figure 4 As shown in the figure, P is well distributed around the material. The good uniformity may be attributed to the melting property of NH4H2PO4 at 300℃. The liquid ammonium salt may diffuse due to surface tension and cover the original NFM particles, which is conducive to the subsequent generation of new sodium salts, achieving the effect of coating and stabilizing the material structure.

[0085] Parameter Test Example 2 Slurry Viscosity Test

[0086] In order to prove that material modification can improve the structural stability of the lifting material and improve the slurry gelation problem during the coating process, NFM positive electrode slurry and NFM-2 positive electrode slurry were prepared according to the same formula (active material: PVDF: Kappa 100 = 95: 2.5: 2.5) and process (dispersion speed of 35 rpm, micro-stirring of 15 rpm); the active material is the positive electrode material prepared in Example 1 (NFM and NFM-2, respectively).

[0087] The material was discharged under the condition of 15% humidity. Considering that the viscometer takes 10-12 minutes to measure the slurry, the viscosity of the slurry was recorded every 25 minutes. Fig. 9 As shown in the figure, the viscosity of the NFM cathode slurry increases almost linearly with the passage of time. The viscosity increases by 5160 mPa s within 2.5 h, while the viscosity of the NFM-2 cathode slurry increases by 1020 mPa s in 50 min and then stabilizes.

[0088] It can be seen that the properties of the material greatly affect the difficulty of processing its slurry. The rising viscosity is not conducive to the subsequent coating of the slurry, and will cause uneven coating and material failure. From the viscosity of the prepared slurry in parameter test Example 2, it can be seen that the prepared slurry has a certain stability at a humidity of 15%, which promotes the improvement of the slurry gelation problem in the subsequent coating process, thereby helping to improve the battery cycle performance. To a certain extent, it is different from controlling the processing conditions of the positive electrode sheet at a humidity of 5-10% to maintain the activity of the positive electrode sheet, which is also beneficial for enterprises to reduce energy consumption.

[0089] Parameter Test Example 3 Material Gram Capacity Test

[0090] The prepared CR2032 button battery was used in the voltage range of 2.0~4.0V (vs Na + / Na), current density 130mAh g-1 (1c), temperature 25°C. The results are as follows Figure 6 shown.

[0091] Figure 5 The first charge and discharge curves of the three samples at 0.1C are shown. There are slight differences in the charge and discharge behaviors of the NFM, NFM-1 and NFM-2 samples.

[0092] Specifically, the charge and discharge behaviors of NFM-1 and NFM samples are similar, which may be due to the simple physical co-coating of NFM and the modifier ammonium salt in NFM-1 sample, and the discharge capacity of NFM-1 sample electrode (132.15 mAh g -1 ) is slightly decreased due to the presence of the ammonium salt coating and the uneven uniformity of the active material. Compared with the NFM sample electrode discharge capacity (139.41 mAh g -1 ), while the discharge capacity of NFM-2 sample electrode (141.42 mAh g -1 ) was slightly improved, and the discharge platform was also increased from the original 2.65V to 2.75V, indicating that the ammonium salt modified NFM was successful.

[0093] Parameter Test Example 4 Material Water Absorption Test

[0094] Table 2 Pole piece weight changes

[0095]

[0096]

[0097] The weight of the six electrode samples of NFM, NFM-1 and NFM-2 samples after coating and vacuum drying at 100℃ for 12h was weighed, and the electrode samples were then placed in a humidity environment of 71% for 16h and weighed (process as shown in Figure 6 The mass of the obtained product after vacuum drying at 100°C for 6 hours was weighed. The results are shown in Table 2.

[0098] As shown in Table 2, by comparing the mass of the pole pieces before and after moisture absorption, it can be found that the mass of the NFM sample, NFM-1 sample, and NFM-2 sample all increased under high humidity conditions, which may be due to the conductive carbon contained in the pole pieces. And interestingly, the mass increase of the NFM-1 sample is the largest, which may be because: simple physical blending only plays a role of physical outer layer coating, and NH4H2PO4 has extremely strong hygroscopicity, which aggravates the moisture absorption failure of the NFM-1 pole piece. The mass increase of the NFM-2 sample pole piece prepared by annealing in the moisture absorption test is the smallest, which may be because the modifier and the sodium ions in the material generate new sodium salts under high temperature conditions. The sodium salts can form sodium salt crystals with water in the air. The water in the crystals can evaporate when dried at high temperature, protecting the oxygen structure of the positive electrode layer.

[0099] In order to further explore the water resistance of the material, the electrode was assembled into a button battery.

[0100] Parameter Test Example 5

[0101] from Figure 7 It can be seen that the first discharge capacity of the NFM-H2O sample is only 54.54 mAh g -1 The test results show that the gram capacity of the NFM sample decreased significantly after moisture absorption; the first discharge capacity of the NFM-1 sample decreased the most, indicating that the simple physical blending of the modifier and the layered oxide material cannot improve the structural stability of the layered oxide material, but has the opposite effect. Unlike the previous two materials, the NFM-2 sample showed good water resistance, indicating that the modified material of the present invention has good structural stability.

[0102] Parameter Test Example 6

[0103] We also investigated the rate performance of NFM samples and NFM-2 samples, as well as the effect of moisture on the rate of NFM-2 samples after exposure to air. Figure 8 As shown in the figure, at a discharge rate of 10C, the NFM-2 sample (95.0~101.46mAh g -1 ) and NFM-2-H2O (83.44~86.81mAh g -1 ) are better than NFM samples (62.21~69.18mAh g -1 ), especially the NFM-2 sample has better rate performance.

[0104] At the same time, it was also found that although the NFM-2 sample had been exposed to air, its rate performance was still better than that of the NFM sample, indicating that the material has excellent stability and has been successfully modified.

[0105] Parameter Test Example 7

[0106] The cycle performance of button cells assembled with NFM samples, NFM-2 samples, and NFM-2-H2O materials was tested at a rate of 1C. The results are as follows: Fig.10 shown.

[0107] Depend on Fig.10 It can be seen that after 50 charge and discharge cycles, the capacity retention rate of the button battery assembled by the NFM sample is 92.36%, that of NFM-2 is 98.02%, and that of NFM-2-H2O is 96.68%. After 100 charge and discharge cycles, the capacity retention rate of the button battery assembled by the NFM sample is 88.89%, that of NFM-2 is 95.01%, and that of NFM-2-H2O is 93.89%.

[0108] In addition, compared with other similar products in the field, such as the prior art CN117546316A, in terms of cycle data, such as the capacity retention rate of the prepared battery after 50 cycles, the button battery capacity retention rate assembled by the NFM-2 sample and the NFM-2-H2O sample of the present application is significantly better than the prior art CN117546316A (50 times, 93.5%). Moreover, the capacity retention rate of the assembled button battery in the present application after 100 cycles is comparable to the capacity retention rate of the battery in CN117546316A after 50 cycles, indicating that the internal structure and chemical composition of the button battery assembled by the NFM-2 sample and the NFM-2-H2O sample prepared in the present application are relatively stable, and can maintain good performance during multiple charge and discharge processes.

[0109] In addition, the present application improves the problem of easy gelation of the positive electrode slurry prepared in the prior art by modifying the positive electrode material, which can help stabilize the density of the coating process. The present application improves the stability of the positive electrode slurry in the air, thereby improving the cycle stability of the battery, so that the battery B prepared in the present application has better electrochemical performance than the battery A in the reference document, that is, it can maintain a good capacity retention rate during multiple charge and discharge processes, which provides a reference case for the subsequent research and development of long-term stable operation of batteries or energy storage systems.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A sodium layered oxide positive electrode material, characterized in that: A base material and a phosphorus-containing compound modified on the surface of base material particles; The matrix material is prepared by mixing solid powder, sodium carbonate and CNTC and then calcining; The phosphorus-containing compound is prepared by mixing a substrate and an ammonium salt, grinding the mixture, sintering the mixture, and cooling the mixture; The ammonium salt is selected from one or more of diammonium phosphate, ammonium hydrogen phosphate, ammonium phosphate and ammonium polyphosphate; The chemical formula of the solid powder is NaTM x O2, TM is a combination of Ni, Fe and Mn, wherein in a stoichiometric ratio, 0.2 < Ni < 0.35, 0.2 < Fe < 0.35, 0.2 < Mn < 0.35; The mass ratio of the matrix material to the phosphorus-containing compound is 100:(0.1-2).

2. The sodium layered oxide positive electrode material according to claim 1, characterized in that: The layered oxide positive electrode material is an O3 type material; The mass ratio of the solid powder, sodium carbonate and CNTC is 100:5:1; The mass ratio of the matrix material to the phosphorus-containing compound is 100:

1.

3. A method for improving the structural stability of the sodium layered oxide positive electrode material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1: Mn source, Fe source and Ni source are uniformly mixed and dissolved in a stoichiometric ratio to obtain a TM salt solution, solid powder is obtained by the action of a coprecipitant, and the solid powder, sodium carbonate and CNTC are mixed and further calcined to obtain a matrix material; S2: mixing and grinding the base material and the ammonium salt; S3: sintering the mixture obtained in S2 and cooling it; The ammonium salt is selected from one or more of diammonium phosphate, ammonium hydrogen phosphate, ammonium phosphate and ammonium polyphosphate.

4. The method according to claim 3, characterized in that: The Mn source, Fe source and Ni source are uniformly mixed in a stoichiometric ratio to prepare 0.6 mol L -1 TM salt solution, where 0.2 < Ni < 0.35, 0.2 < Fe < 0.35, 0.2 < Mn < 0.35; The Mn source, Fe source and Ni source are all corresponding nitrates; The coprecipitant is selected from one or more of sodium carbonate, sodium hydroxide, ammonium carbonate, and sodium bicarbonate; The solid powder, sodium carbonate and CNTC are mixed and calcined in an oxygen atmosphere to obtain a matrix material.

5. The method according to claim 4, characterized in that: The coprecipitant is a mixture of sodium carbonate and sodium hydroxide, and the mass ratio of the two is (20-25):1; The mass ratio of the solid powder, sodium carbonate and CNTC is 100: (1-10): (0.5-3); the solid powder, sodium carbonate and CNTC need to be vacuum dried for 12 h after mixing; The calcination process is: 1 ~ 5 ℃ min -1 Heat to 500 ~ 600 ℃ and calcine for 1 ~ 5 h, then 1 ~ 5 ℃ min -1 Raise the temperature to 900 ~ 1000 ℃ and keep it for 5 ~ 12 h.

6. The method according to claim 3, characterized in that: The mass ratio of the base material to the ammonium salt is 1:(80-120), and the grinding time is 15-25 min.

7. The method according to claim 3, characterized in that: The sintering process is: heating in an inert atmosphere at 1~5℃min -1 Raise the temperature to 300 ~ 400 ℃ and keep warm for 1 ~ 6 h.

8. A positive electrode slurry, characterized in that: Comprising the sodium layered oxide positive electrode material as described in any one of claims 1 to 2.

9. A sodium ion secondary battery, characterized in that: Comprising the positive electrode slurry as claimed in claim 8.

10. Use of the sodium ion secondary battery according to claim 9 in an energy storage device.

Citation Information

Patent Citations

  • Layered oxide cathode materials, their preparation methods, cathode compositions, sodium-ion secondary batteries and their applications

    CN116190633B

  • A sodium-ion battery positive electrode slurry, electrode sheet, and electrode sheet preparation method

    CN116314832B

  • Positive electrode slurry of sodium ion battery, positive electrode plate and sodium ion battery

    CN116525832A

  • Sodium phosphate coated sodium ion positive electrode material as well as preparation method and application thereof

    CN117546316A

  • Positive electrode material, preparation method thereof and sodium ion battery

    CN116504954A